Dissolved and Particulate Barium Distributions Along the US GEOTRACES North Atlantic and East Pacific Zonal Transects (GA03 and GP16): Global Implications for the Marine Barium Cycle. Issue 6 (9th June 2022) - Rahman, Shaily; Shiller, Alan M.; Anderson, Robert F.; Charette, Matthew A.; Hayes, Christopher T.; Gilbert, Melissa; Grissom, Karen R.; Lam, Phoebe J.; Ohnemus, Daniel C.; Pavia, Frank J.; Twining, Benjamin S.; Vivancos, Sebastian M.
Abstract: Processes controlling dissolved barium (dBa) were investigated along the GEOTRACES GA03 North Atlantic and GP16 Eastern Tropical Pacific transects, which traversed similar physical and biogeochemical provinces. Dissolved Ba concentrations are lowest in surface waters (∼35–50 nmol kg −1 ) and increase to 70–80 and 140–150 nmol kg −1 in deep waters of the Atlantic and Pacific transects, respectively. Using water mass mixing models, we estimate conservative mixing that accounts for most of dBa variability in both transects. To examine nonconservative processes, particulate excess Ba (pBaxs ) formation and dissolution rates were tracked by normalizing particulate excess 230 Th activities. Th‐normalized pBaxs fluxes, with barite as the likely phase, have subsurface maxima in the top 1, 000 m (∼100–200 μmol m −2 year −1 average) in both basins. Barite precipitation depletes dBa within oxygen minimum zones from concentrations predicted by water mass mixing, whereas inputs from continental margins, particle dissolution in the water column, and benthic diffusive flux raise dBa above predications. Average pBaxs burial efficiencies along GA03 and GP16 are ∼37% and 17%–100%, respectively, and do not seem to be predicated on barite saturation indices in the overlying water column. Using published values, we reevaluate the global freshwater dBa river input as 6.6 ± 3.9 Gmol year −1 . Estuarine mixing processes may add another 3–13 Gmol year −1 . Dissolved Ba inputs from broad shallow continental margins, previously unaccounted for in global marine summaries, are substantial (∼17 Gmol year −1 ), exceeding terrestrial freshwater inputs. Revising river and shelf dBa inputs may help bring the marine Ba isotope budget more into balance. Key Points: Water mass mixing can account for most dissolved barium (dBa) variations in both Atlantic and Pacific transects Ba inputs to the ocean from broad continental shelves, ∼17 Gmol year −1, are substantial and may bring Ba isotope budget into mass balance Burial efficiencies of Ba, likely as barite, are variable ranging from 17% to 100%